The Authentic Deed that is Degraded due to False Information - Nathanael, Moses; Djajaputra, Gunawan (Law Development Journal, 2025)
An authentic deed is known as the strongest and most legally binding evidence in legal proceedings. However, its integrity can be compromised when fraudulent data is incorporated, leading to the degradation of its evidentiary value. This research aims to analyze the legal implications of authentic deeds that have been degraded due to data falsification and to explore the notary’s responsibility in such cases. This research used normative juridical approach, this study examined statutory regulations, court decisions, and legal doctrines related to document authenticity. The findings indicate that an authentic deed containing falsified data may lose its status as a perfect piece of evidence and be downgraded to an underhand deed, depending on the extent of the forgery. Additionally, notaries may be held accountable if negligence is proven in verifying the validity of the data. This research contributes to a better understanding of the legal protection mechanisms for parties involved in notarial transactions and highlights the importance of strict verification procedures to uphold the authenticity of legal documents.